MicroRNA - Lu, Thomas X.; Rothenberg, Marc E. (Journal of allergy and clinical immunology, 2018)
MicroRNAs (miRNAs) are small endogenous RNAs that regulate gene-expression posttranscriptionally. MiRNA research in allergy is expanding because miRNAs are crucial regulators of gene expression and promising candidates for biomarker development. MiRNA mimics and miRNA inhibitors currently in preclinical development have shown promise as novel therapeutic agents. Multiple technological platforms have been developed for miRNA isolation, miRNA quantitation, miRNA profiling, miRNA target detection, and modulating miRNA levels in vitro and in vivo. Here we will review the major technological platforms with consideration given for the advantages and disadvantages of each platform.